Provenanced Aesthetics: The Beauty of Decay in Dawson City: Frozen Time - Keilty, Patrick (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
Cinema is critical to our understanding of modern archives. Hailed as the permanent record of fleeting moments, cinema emerged at the turn of the 20th century as an unprecedented form of archival knowledge, even as it represented a form of ephemerality in the face of modernity’s increasing rationalization and standardization within archives. So, why are archival studies and cinema studies not in greater conversation with each other? This article allows for a cross-pollination of rigorous methodological and theoretical approaches from cinema studies to add new dimensions to archival theory. Through a close reading of sound, material decay, and film editing, this article argues that Dawson City: Frozen Time reflects the historical symmetry between cinematic and archival impulses to capture the ephemeral while grappling with the material limits of preservation. Dawson City: Frozen Time turns decay into an archival aesthetic not only to convey the way archival records gain meaning when viewed in relation to their unstable custodial histories but also to demonstrate the finitude and distortion of memory and history. Indeed, Dawson City: Frozen Time reframes archives as sites of creative irruption and, specifically, of decay and provenance as aesthetic contrivances that remind us of history’s instability.